(untitled) (Zia e Tahqeeq, 2025)
During the Indian freedom movement, three communities— the Hindus, Muslims and the British Government— were confronted with each other. This ideological as well as realpolitik battle was fought in whole Indian subcontinent. It is ironical that the Muslim community was divided into two schools of thought as far as their response of nationalism was concerned. Some were the proponent of the concept of Indian nationalism and were struggling for India to remain united. While the other strand among the Muslims were the strong supporters of Muslim nationalism and were in the favor of creation of a separate state for the Muslim majority areas culminating in the shape of Pakistan. It was this time when religious and political leadership was struggling for the protection of the rights of Muslim community. These rights were political as well as religious. This article aims at signifying the role of religious leadership especially Sufis or Sajjada Nashins in the freedom movement and the creation of Pakistan. This contribution of Sajjada Nashins was being played at three levels: their personal appeal, their Sufi institutional support and their engagement with the leading Muslim political party i.e. All India Muslim League. This effort has been made to analyze the services of two leading Sufi personalities, Pir Meher Ali Shah and the Pir of Manki Sharif, to highlight their contribution for Muslim community and the creation of Pakistan. The study is exploratory, descriptive and analytical.